Integração regional na onda rosa : entendendo a UNASUL a partir de seu regime internacional regional (RIR) - Yulieth Estefani Martinez Villalba (2020)
This dissertation analyzes the development of the Union of South American Nations (USAN) from the study of its Regional International Regime (RIR). The analytical perspective of the present dissertation is based on the understanding that integration schemes involve the creation of common institutions, that is, RIR. In this sense, our argument is that USAN, as well as other Regional Integration Organizations (RIO), are linked to Regional International Regimes which provide the basis for shaping its organizational architecture. In order to empirically capture the intersubjective component of the RIR, it was necessary to conduct a content analysis of institutional documents registered in the USAN’s digital repository produced by the main decision-making bodies of the organization: The Council of Heads of State and Government (CHSG), the Council of Foreign Ministers (CFM) and the Council of Delegates (CD). The analysis takes 220 institutional texts as primary documents generated from the first South American Presidents' Meeting in 2000 until the last reports in 2018. With a temporal horizon of 18 years, it was possible to perform a longitudinal thematic analysis that allowed us to observe how the main USAN thematic areas have changed over time, as a result of internal dynamics and transformations in the regional and global context. It was possible to show that the rhetorical appeal for the defense of democracy, human rights (DDHH) and the maintenance of regional peace is marked in the documents produced in the early years of the century. However, over time, the valorization of democracy and human rights (DDHH) is losing centrality as UNASUR becomes institutionalized. By analyzing the power relations made official by the contribution rates of USAN's general budget, it was possible to see Brazil's role as the dominant member state and USAN's main paymaster. In this sense, UNASUR's study of the RIR was useful because it helped to understand the substantive bases of its organizational characteristics and contributed to broaden the understanding of its trajectory and evolutionary process.